2022
DOI: 10.1111/jop.13292
|View full text |Cite
|
Sign up to set email alerts
|

N6‐methyladenosine modification contributes to arecoline‐mediated oral submucosal fibrosis

Abstract: Background: Oral submucosal fibrosis (OSF) is a precancerous condition that closely related to the habit of chewing betel nut. The OSF patients of 3%-19% may develop cancer, and this probability is increasing year by year. Epigenetics modifications have been reported as part of the pathogenesis of OSF. However, in OSF field, the role and mechanism of arecoline-induced activation of transforming growth factor β (TGF-β) signaling on N6-methyladenosine (m6A) modification remain unclear. In this study, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…To investigate the possible interaction between Epi1.2 and T cells in the development of OSF, we established an Epi1.2 cell model of OSF in vitro using arecoline, a primary component implicated in the progression of OSF [ 35 , 36 ]. CCK8 assays and scratch tests were conducted to evaluate the impact of different concentrations of arecoline solution on the proliferation and migration of epithelial cells (HOK) over 48 h. The results showed that high concentrations of arecoline (60 µg/mL, 80 µg/mL) stimulated the proliferation of epithelial cells within the first 24 h. The proliferation ability of HOK cells could be decreased by a high concentration arecoline solution, as compared to the low concentration (20 µg/mL, 40 µg/mL) solution after 48 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the possible interaction between Epi1.2 and T cells in the development of OSF, we established an Epi1.2 cell model of OSF in vitro using arecoline, a primary component implicated in the progression of OSF [ 35 , 36 ]. CCK8 assays and scratch tests were conducted to evaluate the impact of different concentrations of arecoline solution on the proliferation and migration of epithelial cells (HOK) over 48 h. The results showed that high concentrations of arecoline (60 µg/mL, 80 µg/mL) stimulated the proliferation of epithelial cells within the first 24 h. The proliferation ability of HOK cells could be decreased by a high concentration arecoline solution, as compared to the low concentration (20 µg/mL, 40 µg/mL) solution after 48 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the status of m 6 A modification and its relationship with m 6 A regulator expression have not been studied. Although the overall m 6 A modification was enhanced in precancerous oral submucosal fibrosis, the target genes and corresponding regulatory factors were unclear ( 29 ). In this study, we used a well-established precancerous cell line ( 30 ) as a model to investigate the potential contribution of m 6 A modification to the initiation of cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Oral submucosal fibrosis (OSF) is a precancerous condition. Compared with normal tissues, the overall m 6 A level in OSF tissues was increased, suggesting that m 6 A modification contributes to OSF ( 29 ). However, to our knowledge, the change of m 6 A profile and the expression of m 6 A regulators in precancerous cells have not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The relative gene expressions were calculated in accordance with the 2 ΔΔCt method. The methylated m6A RNA immunoprecipitation (me-RIP) assay was performed as described previously [24]. Relevant primer information was listed in Table 1.…”
Section: Lentivirus Infection Of Neuronsmentioning
confidence: 99%